1967
DOI: 10.1002/ctpp.19670070307
|View full text |Cite
|
Sign up to set email alerts
|

Quantenstatistik des Hochtemperatur‐Plasmas im thermodynamischen Gleichgewicht

Abstract: A b s t r a c tHigh temperature plasmas are investigated on the basis of quantum theory. A new method for the calculation of the thermodynamic properties is developed. According to the method of MORITA effective potentials are introduced. They permit the evaluation of the partition function with the well-known formalism of classical statistical mechanics. The first corrections added to DEBYE'S limiting law of the free energy are expressed by the two particle SLATER sum S,(T).A BLOCH equation for S,(r) is deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
2

Year Published

1968
1968
2010
2010

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 11 publications
5
32
0
2
Order By: Relevance
“…Among the presently known formulas, to our knowledge the equation (47) represents the best approximation of the excess free energy of high temperature electron-ion-plasmas until the third virial coefficient. The results of Ebeling et al [15] and Ebeling et al [16] are in agreement with the corresponding terms in eq. (47) until the second virial coefficient.…”
Section: The Quantum Second Virial Coefficientsupporting
confidence: 81%
“…Among the presently known formulas, to our knowledge the equation (47) represents the best approximation of the excess free energy of high temperature electron-ion-plasmas until the third virial coefficient. The results of Ebeling et al [15] and Ebeling et al [16] are in agreement with the corresponding terms in eq. (47) until the second virial coefficient.…”
Section: The Quantum Second Virial Coefficientsupporting
confidence: 81%
“…Every N -particle hightemperature density matrix is represented as a product of two-particle density matrices. For the two-particle density matrix there is an analytical solution of the Bloch equation by first-order perturbation theory [17]:…”
Section: Direct Path Integral Monte Carlomentioning
confidence: 99%
“…In the high-temperature limit, ρ ab factorizes into a kinetic (ρ 0 ) and an interaction term (ρ ab U ), ρ ab ≈ ρ 0 ρ ab U , because it can be shown that [40,41] …”
Section: High-temperature Asymptotics Of the Density Matrix In Tmentioning
confidence: 99%
“…We calculated the effective potential by solving a Bloch equation by first order perturbation theory. The method has been described in detail in [41]. This procedure defines an effective off-diagonal quantum pair potential for Coulomb systems, which depends on the inter-particle distances r ab , r ′ ab .…”
Section: High-temperature Asymptotics Of the Density Matrix In Tmentioning
confidence: 99%